Neighbour home gardening predicts dietary diversity among rural Tanzanian women. Issue 9 (12th February 2019) - Blakstad, Mia M; Bellows, Alexandra L; Mosha, Dominic; Canavan, Chelsey R; Mlalama, Killian; Kinabo, Joyce; Kruk, Margaret E; Masanja, Honorati; Fawzi, Wafaie W
Abstract: Objective: The present study's aim was to assess the impact of a nutrition-sensitive intervention on dietary diversity and home gardening among non-participants residing within intervention communities. Design: The study was a cross-sectional risk factor analysis using linear and logistic multivariate models. Setting: In Tanzania, women and children often consume monotonous diets of poor nutritional value primarily because of physical or financial inaccessibility or low awareness of healthy foods. Participants: Participants were women of reproductive age (18–49 years) in rural Tanzania. Results: Mean dietary diversity was low with women consuming three out of ten possible food groups. Only 23·4 % of respondents achieved the recommended minimum dietary diversity of five or more food groups out of ten per day. Compared with those who did not, respondents who had a neighbour who grew crops in their home garden were 2·71 times more likely to achieve minimum dietary diversity (95 % CI 1·60, 4·59; P =0·0004) and 1·91 times more likely to grow a home garden themselves (95 % CI 1·10, 3·33; P =0·02). Other significant predictors of higher dietary diversity were respondent age, education and wealth, and number of crops grown. Conclusions: These results suggest that there are substantial positive externalities of home garden interventions beyond those attained by the people who own and grow the vegetables. Cost-effectiveness assessments of nutrition-sensitive agriculture, including home garden interventions, should factor in the effects on the community, and not just on the individual households receiving the intervention.